A Phase I, Randomized, Double-Blind, Placebo-Controlled, Single Ascending Dose, Multiple Dose, and Food Effect Trial of the Safety, Tolerability and Pharmacokinetics of Highly Purified Cannabidiol in Healthy Subjects - Taylor, Lesley; Gidal, Barry; Blakey, Graham; Tayo, Bola; Morrison, Gilmour (CNS drugs, 2018)
Background A formal single ascending and multiple dose pharmacokinetic (PK) trial of cannabidiol (CBD) oral solution was required to determine the safety and tolerability of CBD, the maximum tolerated dose, and to examine the effect of food on CBD PK parameters. Objective This trial assessed the safety, tolerability and PK of CBD oral solution in healthy adult volunteers, as well as the effect of food on CBD PK parameters. Methods The study consisted of three arms: single ascending dose (1500, 3000, 4500 or 6000 mg CBD [ n = 6 per group]/placebo [ n = 8; 2 per CBD dose group]), multiple dose (750 or 1500 mg CBD [ n = 9 per group]/placebo [ n = 6; 3 per CBD dose group] twice daily), and food effect (1500 mg CBD single dose [ n = 12]). All subjects completed all trial arms and were analyzed as planned. Results CBD was generally well tolerated. Diarrhea, nausea, headache, and somnolence were the most common adverse events (AEs) across all trial arms, with an increased incidence of some gastrointestinal and nervous system disorder AEs (most notably diarrhea and headache) apparent in subjects taking CBD compared with placebo. All AEs were of mild or moderate severity; none were severe or serious. There were no deaths or discontinuations in the trial. After single oral doses, CBD appeared rapidly in plasma; time to maximum plasma concentration ( t max ) was approximately 4–5 h. The major circulating metabolite was 7-carboxy-CBD, then parent CBD, 7-hydroxy-CBD (active metabolite), and 6-hydroxy-CBD (a relatively minor metabolite). Plasma exposure to CBD [maximum plasma concentration ( C max ) and area under the plasma concentration-time curve from time zero to time t (AUC t )] increased in a less than dose-proportional manner ( C max slope 0.73; AUC t slope 0.64). Oral clearance of CBD was high (1111–1909 L/h) and apparent volume of distribution was large (20,963–42,849 L). CBD reached steady state after approximately 2 days, with moderate accumulation (1.8- to 2.6-fold) after 750 and 1500 mg CBD twice daily. After 7 days, a twofold increase in CBD dose resulted in 1.6- and 1.9-fold increases in geometric mean C max and area under the plasma concentration-time curve over a dosing interval (AUC τ ), respectively. CBD elimination was multiphasic; the terminal elimination half-life was approximately 60 h after 750 and 1500 mg CBD twice daily; and effective half-life estimates ranged from 10 to 17 h. C max was 541.2 ng/mL and AUC τ was 3236 ng·h/mL after 1500 mg CBD twice daily. A high-fat meal increased CBD plasma exposure ( C max and AUC t ) by 4.85- and 4.2-fold, respectively; there was no effect of food on t max or terminal half-life. Conclusion CBD was generally well tolerated. Most AEs were mild in severity; none were severe or serious. The safety and PK profile support twice-daily administration of CBD.